Development of Item Bank Management and Multiple Choice Analysis via Internet - Chaidee, Kamonlak; Kongmun, Kwanjai; Sudnalao, Khunnithee; Sukmai, Chanachon (Journal of Advanced Development in Engineering and Science, 2023)
Objectives of this study are to develop an item bank management and an item analysis system on internet. Problems of traditional working system and user requirements are analyzed. A new working system is designed and developed using PHP and MySQL for 3 groups which are teachers, students and an administrator. The item analysis system can be used to calculate a reliability value by using Kuder-Richardson formular, K-R20 and K-R21, and a level of difficulty and a power of discrimination by using a choice analysis technique with 25, 27, 33 and 50 percentage of upper and lower groups that a choosing depend on number of sample group. Errors of system operating were tested and accuracy of the system was measured by comparision with traditional item analysis that results were not different. The system was tested with the sample group of 53 people. Satistaction evaluation was performed by using questionnaires. The satisfaction of the administrator is in the highest level, while techers and students is in the high level.